Determinants of users’ continuance intention of digital museums: a self-regulation perspective - Zhang, Binyuan; Jia, Tingting; Zhang, Wenhui (Frontiers in Public Health, 2024)
Driven by modern technological innovations (virtual reality, augmented reality, mixed reality and interactive 3D, etc.), digital museums open up new modes of user visitation through virtual exhibition halls and interactive technologies, thus bridging the gap between the museums and their users for in-depth communication. This study explores the determinants of users’ continuance intention to use digital museums based on Bagozzi’s self-regulation framework. We found that appraisal factors (interaction quality, media richness, and information quality) were strong predictors of emotional reaction (satisfaction and perceived playfulness). In particular, media richness and information quality had significant effects on both satisfaction and perceived playfulness. However, interaction quality only positively affected satisfaction. Both satisfaction and perceived playfulness positively influence users’ continuance intention to use digital museums. These findings enrich the literature on digital museums, offer new perspectives and supplements to existing research on user behavior in digital museums, thereby assisting developers and operators of digital museums in more effectively designing their digital systems and enhancing user experience.